Are category labels primary? Children use similarities to reason about social groups. Issue 2 (7th August 2020) - Jordan, Ashley; Dunham, Yarrow
Abstract: While interpersonal similarities impact young children's peer judgments, little work has assessed whether they also guide group‐based reasoning. A common assumption has been that category labels rather than 'mere' similarities are unique constituents of such reasoning; the present work challenges this. Children (ages 3–9) viewed groups defined by category labels or shared preferences, and their social inferences were assessed. By age 5, children used both types of information to licence predictions about preferences (Study 1, n = 129) and richer forms of coalitional structure (Study 2, n = 205). Low‐level explanations could not account for this pattern (Study 3, n = 72). Finally, older but not younger children privileged labelled categories when they were pitted against similarity (Study 4, n = 51). These studies show that young children use shared preferences to reason about relationships and coalitional structure, suggesting that similarities are central to the emergence of group representations. Abstract : Children (ages 3–9) viewed groups defined by labelled categories or shared preferences, and their social inferences were assessed. By age 5, children used both types of information to licence predictions about preferences and richer forms of coalitional structure. Low‐level explanations could not account for this pattern. Older but not younger children privileged category labels when they were pitted directly against shared preference.